2019
DOI: 10.7554/elife.49853
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity of oligomeric β-propellers with different numbers of identical blades

Abstract: β-Propellers arise through the amplification of a supersecondary structure element called a blade. This process produces toroids of between four and twelve repeats, which are almost always arranged sequentially in a single polypeptide chain. We found that new propellers evolve continuously by amplification from single blades. We therefore investigated whether such nascent propellers can fold as homo-oligomers before they have been fully amplified within a single chain. One- to six-bladed building blocks derive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…A similar shift in symmetry is brought about by making tandem copies of the protein [25]. Similar structural plasticity in fragment assembly has also been shown in β‐propellers in a study last year by the group of Lupas, which addressed the question of structural diversity in propellers with different numbers of identical blades [16]. Stable proteins were created by expressing tandem copies of a blade, based on the natural 7‐bladed propeller PkwA, as a single polypeptide.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A similar shift in symmetry is brought about by making tandem copies of the protein [25]. Similar structural plasticity in fragment assembly has also been shown in β‐propellers in a study last year by the group of Lupas, which addressed the question of structural diversity in propellers with different numbers of identical blades [16]. Stable proteins were created by expressing tandem copies of a blade, based on the natural 7‐bladed propeller PkwA, as a single polypeptide.…”
Section: Discussionmentioning
confidence: 82%
“…The multimeric WRAP assemblies were not symmetrically arranged around a central axis, and it seems that the interface between fragments also provides some structural flexibility. Although fragments could assemble into 8‐ and 9‐bladed propellers, it is unclear whether monomeric constructs would adopt the same conformations [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As repeat proteins, β-propellers provide us with both analytic and synthetic approaches to understanding their evolutionary origins. In a recent paper, for example, Lupas and colleagues used WRAP to show that β-propellers built from identical repeat sequences can show remarkable structural plasticity [21]. They expressed tandem repeats of this blade with up to six copies per polypeptide.…”
Section: Repeatsmentioning
confidence: 99%
“…Despite their wide sequence diversity ( Fig. 1e, f ), most β-propeller families are related to each other and emerged by independent amplification from a set of homologous ancestral blades, in a process that is still visibly ongoing ( Afanasieva et al , 2019 ; Alva et al , 2015 ; Chaudhuri et al , 2008 ; Dunin-Horkawicz et al , 2014 ; Kopec and Lupas, 2013 ). Classification studies ( Chaudhuri et al , 2008 ; Kopec and Lupas, 2013 ) suggested that most β-propeller families form a supercluster centred on WD40 β-propellers, a large superfamily characterized by a Trp-Asp motif at the end of strand C (in position 40).…”
Section: Introductionmentioning
confidence: 99%